Diasporic Translations of Greek Women’s Poetry in Anthologies: The Role of the (Migrant) Translator-Anthologist. - Velasco-Urquiza, Natalia (My University, 2026)
Since the 1980s, feminist translation studies have sought to recover and foreground the silenced works of women writers. In recent decades, the growing visibility of women’s writing within the literary marketplace has made anthologies of women’s writing in translation particularly significant objects of study, as they reveal the power structures embedded in both translation and anthologizing practices. Such anthologies often function as feminist translation artifacts—not only by reclaiming women’s voices marginalized by patriarchy but also by foregrounding the visibility and authorship of the translator(-anthologist) and the critical role of metatextual commentary. Yet, feminist translation is not immune to the forces of the literary market and its selective mechanisms of cultural production. This paper examines the pivotal role of (migrant) women translator-anthologists in challenging “West-to-the-rest” narratives through their translation and curation of women authors writing in non-dominant languages and from marginalized literary traditions. Specifically, it investigates anthologies of Greek women’s poetry translated into English and Spanish. Drawing on transnational feminist translation studies, the analysis focuses on the agency and identity of migrant women translators—traced through the metatexts and peritexts of their editions—who spearheaded the first initiatives in these languages to recover and assemble the voices of contemporary Greek women poets excluded from mainstream translation and general anthologies of Greek literature. Ultimately, this study underscores the significance of translator identity within feminist translation practices and contributes to the still limited scholarship on feminist translation strategies and functions as they manifest in anthologies of women’s writing in translation.
Keywords: Traducción; Literatura griega moderna; Feminismo; Feminist translation; Translation anthologies; Modern Greek literature; Translator studies; Translation and diaspora